Determinants of Polyandry: An Analysis of Polyandrous Families in Shillai Tehsil, Himachal Pradesh - Kumar, Shiv; Kumar, Thakur Prem (Journal of Neonatal Surgery, 2025)
Polyandry, a rare but historically significant marital system, has been practiced in various regions of the world, including parts of India. This study examines the determinants influencing the persistence and transformation of polyandry among families in Shillai Tehsil, Himachal Pradesh. While much of the existing research has focused on the historical and cultural dimensions of polyandry, limited empirical studies have explored its contemporary relevance. This study employs a quantitative approach, utilizing factor analysis to identify the key social, economic, and cultural factors affecting polyandrous practices in the region. The research was conducted in Shillai Tehsil, a region known for its historical prevalence of polyandry, where a sample of 36 respondents from polyandrous families was selected. Primary data was collected through in-depth interviews and structured surveys, capturing perspectives on marital roles, familial structures, economic conditions, and evolving societal attitudes. Thematic analysis and coding techniques were employed to categorize responses, followed by factor analysis to uncover dominant determinants. The findings indicate that economic stability, land inheritance practices, familial obligations, and cultural traditions play a crucial role in sustaining polyandry, while modernization, legal awareness, and shifting gender norms contribute to its decline. Additionally, the study reveals that polyandrous families experience unique interpersonal and social challenges, such as power dynamics, emotional adjustments, and societal stigma. However, many respondents emphasized the practical advantages of polyandry, including shared financial responsibilities and resource management. The results also highlight the interplay between economic necessity and cultural continuity, suggesting that polyandry is not merely a relic of the past but an evolving institution influenced by broader social transformations. By filling a critical research gap, this study provides a contemporary perspective on polyandry in Himachal Pradesh, offering valuable insights for scholars, policymakers, and social anthropologists. Understanding the determinants of polyandry in this region contributes to broader discussions on marriage systems, gender roles, and family dynamics in India. Future research should further explore the legal and psychological dimensions of polyandrous relationships, particularly in relation to changing societal norms.